Implementation of Design Thinking Method on User Interface Design of Digital Police Information System Application (SIPOLDI) - Yuliani, Sari; Fadilah, Evi (International Journal of Education, Information Technology, and Others, 2024)
This research aims to design the User Interface of the POLDA Digital Information System by implementing the Design Thinking method. In the research, the Design Thinking method was used. Design Thinking is an innovative approach that focuses on human needs, adopted from design practices, and integrates aspects such as user needs, technical possibilities, and success requirements. The results showed several key issues, including difficult system navigation, suboptimal document search features, and the absence of automatic notifications. These issues were the main concerns in the user interface design, and solutions to these issues included simplifying navigation, developing a more efficient search feature, and adding automated notification elements. By implementing these solutions, SIPOLDI is expected to improve the user experience of this application.